Abiotic methane seepage in the Ronda peridotite massif, southern Spain. (March 2016) - Etiope, G.; Vadillo, I.; Whiticar, M.J.; Marques, J.M.; Carreira, P.M.; Tiago, I.; Benavente, J.; Jiménez, P.; Urresti, B.
Abstract: Abiotic methane in serpentinized peridotites (MSP) has implications for energy resource exploration, planetary geology, subsurface microbiology and astrobiology. Once considered a rare occurrence on Earth, reports of MSP are increasing for numerous localities worldwide in low temperature, land-based springs and seeps. We report the discovery of six methane-rich water springs and two ponds with active gas bubbling in the Ronda peridotite massif, in southern Spain. Water is hyperalkaline with typical hydrochemical features of active serpentinization (pH: 10.7 to 11.7, T: 17.1 to 21.5 °C, Ca–OH facies ). Dissolved CH4 concentrations range from 0.1 to 3.2 mg/L. The methane stable C and H isotope ratios in the natural spring and bubbling sites (δ 13 CCH4 : −12.3 to −37‰ VPDB; δ 2 HCH4 : −280 to −333‰ VSMOW) indicate a predominant abiotic origin. In contrast, springs with manmade water systems, i.e., pipes or fountains, appear to have mixed biotic-abiotic origin (δ 13 CCH4 : −44 to −69‰; δ 2 HCH4 : −180 to −319‰). Radiocarbon ( 14 C) analyses show that methane C in a natural spring is older than ca. 50, 000 y BP, whereas dissolved inorganic carbon (DIC) analysed in all springs has an apparent 14 C age ranging from modern to 2334 y BP. Therefore most, if not all, of the CH4 is allochthonous, i.e., not generated from the carbon in the hyperalkaline water. Methane is also released as bubbles in natural ponds and as diffuse seepages (∼10 1 –10 2  mg CH4 m −2 d −1 ) from the ground up to several tens of metres from the seeps and springs, albeit with no overt visual evidence. These data suggest that the gas follows independent migration pathways, potentially along faults or fracture systems, physically isolated from the hyperalkaline springs. Methane does not seem to be genetically related to the hyperalkaline water, which may only act as a carrier of the gas. Gas-bearing springs, vents and invisible microseepage in land-based peridotites are more common than previously thought. In addition to other geological sources, MSP is potentially a natural source of methane for the troposphere and requires more worldwide flux measurements. Highlights: Methane-rich water springs and seeps discovered in the Ronda peridotite massif. Stable C and H isotope ratios indicate a predominant abiotic origin of methane. Methane is not generated from the C in the hyperalkaline water. Methane is released as bubbles and diffuse seepages. Gas follows migration pathways independent from the hyperalkaline springs.